Elite boxers' psychophysiology conditioning system efficiency improvement - Shayakhmetova, E. S.; Khakimov, E. R.; Gainullina, A. F.; Lintvarev, A. L. (Theory and Practice of Physical Culture, 2018)
The study was designed to obtain and analyse cardiovascular and nervous system functionality data of elite boxers by means of the modern biological feedback technologies. The subject boxers were tested in the competitive periods of 2015-16 at Bashkir State Pedagogical University named after M. Akmulla in cooperation with the Psychophysiology and Experimental Psychology Laboratory. Subject to the study were elite boxers (n=68) split up into Experimental (EG) and Reference Groups (RG) of 34 people each. The EG training process included a psychophysiology conditioning component based on the relevant biological feedback (BFB) technologies using the `Reacor-T` System. The study data and analyses demonstrated benefits of the BFB technologies as verified by clear improvements in the cardiovascular and nervous system functionality rates.